Model production of corn development for industrial needs and increasing economy. Issue 1 (April 2020) - Panikkai, Sumarni; Azrai, M.; Fahmi, Femmi N.
Abstract: Regional economic development has many aspects that continue to change dynamically, planned and coordinated when viewed from a planning framework of the regional economic development, whether regionally, nationally or internationally. The regional economic development is aimed to the achievement of national development sub-system targets that organized territorially or spatially. The research method that was used is a dynamic system approach. The data used are secondary data obtained from various instances. Method of data analysis used dynamic system software. The results showed exponential growth trend of maize production. The pattern illustrates that an increase in national maize production over time. Model simulation results were acquired by using government intelligence strategy capable of increasing corn production and increase province economy. From extensification increase simulation results of 1.6 eh / year, it is capable of increasing corn production exceeding government's target of 24, 8 million ton in 2020, unable to fulfil the requirement of corn that increasing faster than corn production. The increase of national corn production will chip in towards farmer income, which indirectly contributes towards PDB until national economy.